EULAR recommendations for patient education for people with inflammatory arthritis - Zangi, Heidi A; Ndosi, Mwidimi; Adams, Jo; Andersen, Lena; Bode, Christina; Boström, Carina; van Eijk-Hustings, Yvonne; Gossec, Laure; Korandová, Jana; Mendes, Gabriel; Niedermann, Karin; Primdahl, Jette; et al. (Annals of the rheumatic diseases, 2015)
OBJECTIVES: The task force aimed to: (1) develop evidence-based recommendations for patient education (PE) for people with inflammatory arthritis, (2) identify the need for further research on PE and (3) determine health professionals' educational needs in order to provide evidence-based PE. METHODS: A multidisciplinary task force, representing 10 European countries, formulated a definition for PE and 10 research questions that guided a systematic literature review (SLR). The results from the SLR were discussed and used as a basis for developing the recommendations, a research agenda and an educational agenda. The recommendations were categorised according to level and strength of evidence graded from A (highest) to D (lowest). Task force members rated their agreement with each recommendation from 0 (total disagreement) to 10 (total agreement). RESULTS: Based on the SLR and expert opinions, eight recommendations were developed, four with strength A evidence. The recommendations addressed when and by whom PE should be offered, modes and methods of delivery, theoretical framework, outcomes and evaluation. A high level of agreement was achieved for all recommendations (mean range 9.4-9.8). The task force proposed a research agenda and an educational agenda. CONCLUSIONS: The eight evidence-based and expert opinion-based recommendations for PE for people with inflammatory arthritis are intended to provide a core framework for the delivery of PE and training for health professionals in delivering PE across Europe.
Keywords: ankylózující spondylitida; Humans; Clinical Competence; revmatické nemoci; poradní výbory; Evropa; Arthritis, Rheumatoid; Advisory Committees; revmatologie; Patient Education as Topic; lidé; Europe; klinické kompetence; Arthritis; medicína založená na důkazech; revmatoidní artritida; Rheumatic Diseases; Spondylitis, Ankylosing; artritida; Patient perspective; Multidisciplinary team-care; vzdělávání pacientů jako téma; Rheumatology; Evidence-Based Medicine